2017
DOI: 10.5194/tc-11-1173-2017
|View full text |Cite
|
Sign up to set email alerts
|

A multiphysical ensemble system of numerical snow modelling

Abstract: Abstract. Physically based multilayer snowpack models suffer from various modelling errors. To represent these errors, we built the new multiphysical ensemble system ES-CROC (Ensemble System Crocus) by implementing new representations of different physical processes in the deterministic coupled multilayer ground/snowpack model SUR-FEX/ISBA/Crocus. This ensemble was driven and evaluated at Col de Porte (1325 m a.s.l., French alps) over 18 years with a high-quality meteorological and snow data set. A total numbe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
156
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(162 citation statements)
references
References 73 publications
3
156
0
3
Order By: Relevance
“…These results endorse the idea that snowpack ensemble simulations are necessary to mitigate error compensations, as recently developed for Crocus with ESCROC (Ensemble System Crocus; Lafaysse et al, 2017).…”
supporting
confidence: 57%
See 2 more Smart Citations
“…These results endorse the idea that snowpack ensemble simulations are necessary to mitigate error compensations, as recently developed for Crocus with ESCROC (Ensemble System Crocus; Lafaysse et al, 2017).…”
supporting
confidence: 57%
“…The parametrisation of the albedo evolu-485 tion also needs to be questioned: Lafaysse et al (2017) underlined a positive bias of Crocussimulated albedo at Col de Porte (Fig. 1a), which they partly attributed to the parametrisation of albedo decrease in the visible range as a function of the age of the snow layer and the altitude of the site.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In our survey, the few land surfaceatmosphere integrated process-oriented models like PIHM and Parflow-CLM were exceptional in the level of integration and 25 application of observation network data. Along with a few other examples (e.g., Boone et al, 2009;Lafaysse et al, 2017), land surface models are rarely used to model processes with an integrated approach embracing biotic and abiotic variables using LTER/CZO data. A stronger communication between land surface modellers and LTER/CZO communities would enhance the integration of in-situ observations in models, but is challenged by the continental-to-global focus of land surface models versus the site-to-region focus of LTER/CZO observatories.…”
mentioning
confidence: 99%
“…Underestimated melting was also found by QuĂ©no et al (2016QuĂ©no et al ( , 2017 and Vionnet et al (2016), and complementary studies are needed to investigate the cause of this issue. Lafaysse et al (2017) developed an ensemble snowpack model using SURFEX/Crocus called ESCROC (Ensemble System 10 Crocus) to address modeling errors. They found that by using optimal members they were able to more than half of simulation errors, and those ensembles have a significantly better predictive power than the classical deterministic approach.…”
mentioning
confidence: 99%